2017
DOI: 10.1155/2017/4730878
|View full text |Cite
|
Sign up to set email alerts
|

trans‐Cinnamaldehyde Inhibits Microglial Activation and Improves Neuronal Survival against Neuroinflammation in BV2 Microglial Cells with Lipopolysaccharide Stimulation

Abstract: Background Microglial activation contributes to neuroinflammation and neuronal damage in neurodegenerative disorders including Alzheimer's and Parkinson's diseases. It has been suggested that neurodegenerative disorders may be improved if neuroinflammation can be controlled. trans-cinnamaldehyde (TCA) isolated from the stem bark of Cinnamomum cassia possesses potent anti-inflammatory capability; we thus tested whether TCA presents neuroprotective effects on improving neuronal survival by inhibiting neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…This outcome may be attributed to the reduction in proinflammatory and oxidant factors as there are several reports on the antioxidant and anti-inflammatory effects of Cin [Pyo et al, 2013;Chen et al, 2016;Fu et al, 2017;Roghani et al, 2017], confirming the present findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This outcome may be attributed to the reduction in proinflammatory and oxidant factors as there are several reports on the antioxidant and anti-inflammatory effects of Cin [Pyo et al, 2013;Chen et al, 2016;Fu et al, 2017;Roghani et al, 2017], confirming the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Ho et al [2013] reported that cinnamon had a promising therapeutic influence on neurodegenerative diseases, and Cin had the highest antineuroinflammatory property among various examined compounds. The above studies totally proved the regenerative impact of Cin and the increasing functional recovery in CNS injury [Pyo et al, 2013;Chen et al, 2016;Fu et al, 2017;Roghani et al, 2017]. Cin has been shown to be a natural antiinflammatory and antioxidant agent that may be advantageous in protecting neurons against Alzheimer and Parkinson disease [Peterson et al, 2009;Roghani et al, 2017].…”
Section: Discussionmentioning
confidence: 93%
“…TCA is an effective treatment for neurodegenerative diseases, such as cerebral ischemic injury [21]. In addition, TCA inhibits the microglial activation and improves the neuronal survival against neuroinflammation in BV2 microglial cells with LPS stimulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…TCA has a certain antineuroinflammatory effect, and its protective effect on dopaminergic neurons may be related to the inhibition of inflammation [19]. TCA inhibits microglia activation and inflammatory response induced by lipopolysaccharide (LPS) [20]. TCA reduces neuroinflammation via inhibiting NF-κB pathway [21].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 2'-hydroxy cinnamaldehyde derived from the bark of Cinnamomum cassia has been found to inhibit the transcriptional activity of nuclear factor (NF) -kB and production of nitric oxide (NO) in lipopolysaccharide-induced inflammation models [17]. A recent study has shown that trans-cinnamaldehyde obtained from Cinnamomum cassia bark suppressed activation of microglia and the neuroinflammatory process by inhibiting the production of NO and expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and interleukin-1β (IL-1β) [18]. Furthermore, administration of ethanol extract of CZ has been found to inhibit the intracellular release of tumor necrosis factor-alpha (TNF-α) and TNF-α gene expression, suggesting its anti-inflammatory property [19].…”
Section: Introductionmentioning
confidence: 99%